Dinamika Judi Di Indonesia: Sejarah Judi Sebagai Dongkrak Perekonomian Indonesia Tahun 1960-1994 - Nayla Zulfia; Dinda Ayu Fitriani; Miftah Uswatun Hasanah; Riki Irawan (Academica: Journal of Multidisciplinary Studies, 2023)
After its independence, Indonesia continues to experience many problems from various fields, be it educational, economic, social, or other fields. Moreover, at that time human resources were still low. Under the pretext of developing the economy, lotteries and sweepstakes were legalized by the government, even though this is against the teachings of Islam, which is the majority in Indonesia. This research will discuss the background to the legalization of the SDSB (Social Generous Contribution/ Sumbangan Dermawan Sosial Berhadiah) lottery or sweepstakes with prizes) in 1960-1994 and its impact. This study uses qualitative methods with historical and ethnographic approaches. Based on the law and the MUI fatwa (Indonesian Ulema Council/Majelis Ulama Indonesia) which regulates gambling, this is prohibited. The implication of this research is that it is expected to be able to provide an in-depth understanding of the social, cultural, political and economic fields of the existence of lottery and sweepstakes policies in Indonesia, and their impact on Indonesian society. This research is expected to be able to contribute to the development of science and the history of gambling in Indonesia and provide input for the government and society in overcoming gambling problems in Indonesia.